Psychometric Evaluation of the Young Children's Participation and Environment Measure (YC-PEM) for use in Singapore. (27th May 2018) - Lim, Chun Yi; Law, Mary; Khetani, Mary; Rosenbaum, Peter; Pollock, Nancy
ABSTRACT: Aims : To estimate the psychometric properties of a culturally adapted version of the Young Children's Participation and Environment Measure (YC-PEM) for use among Singaporean families. Methods : This is a prospective cohort study. Caregivers of 151 Singaporean children with (n = 83) and without (n = 68) developmental disabilities, between 0 and 7 years, completed the YC-PEM (Singapore) questionnaire with 3 participation scales (frequency, involvement, and change desired) and 1 environment scale for three settings: home, childcare/preschool, and community. Setting-specific estimates of internal consistency, test-retest reliability, and construct validity were obtained. Results : Internal consistency estimates varied from .59 to .92 for the participation scales and .73 to .79 for the environment scale. Test-retest reliability estimates from the YC-PEM conducted on two occasions, 2–3 weeks apart, varied from .39 to .89 for the participation scales and from .65 to .80 for the environment scale. Moderate to large differences were found in participation and perceived environmental support between children with and without a disability. Conclusions : YC-PEM (Singapore) scales have adequate psychometric properties except for low internal consistency for the childcare/preschool participation frequency scale and low test-retest reliability for home participation frequency scale. The YC-PEM (Singapore) may be used for population-level studies involving young children with and without developmental disabilities.